SYRPHID FLIES (DIPTERA: SYRPHIDAE) AT UNIVERSITY CAMPUS OF PERAYOC, CUSCO, PERU - Aucca, Lourdes (2021)
The presence of five species of Syrphidae is registered at university campus of the National University of San Antonio Abad del Cusco, Peru. The collection was made using an entomological net and a vacuum cleaner. The identifications were achieved using specialized keys. The abundances of the five species found were evaluated in four sectors of the campus. The identified species correspond to Eupeodes (Metasyrphus) sp., Allograpta sp., Platycheirus (Carposcalis) chalconotus (Philippi, 1865), Toxomerus sp. and Eristalis bogotensis Macquart, 1842.